An Investigation in Teaching Strategies: a Process-Genre Model to Promote Students’ Writing skills Case of Third Year EFL Students at the University of Bejaia - imerzoukene, sonia; ameziane, hamid; guendouzi, amar (Journal of Social Sciences and Humanities, 2021)
This paper aims to adapt a process-genre model, based on Badger and White (2000), to 34 third year students of English at the university of Bejaia in order to develop their writing skills. The model is implemented as an alternative to develop students’ writing skills as it is based on the principles of the product, process and genre approaches to teaching writing. The researcher introduced four types of writing (expository, narrative, descriptive and writing), accomplished in 180 minutes each. The model proposed is based on seven-7 steps: preparation; modelling; planning; collaborative writing; independent writing; Revision and Assessment. The study is based on students’ essays evaluated on the basis of an essay assessment rubric (ReadWriteThink). This latter encompasses the main elements of writing investigated in this paper (Focus and Details; Organization; Voice; Word Choice; and Sentence Structure, Grammar, Mechanics and Spelling). The results revealed the effectiveness of the process-genre model as students developed in a significant way their writing skills.